SISTEMA CONSTRUTIVO LIGHT WOOD FRAME COMO ALTERNATIVA PARA REDUÇÃO DOS RESÍDUOS DA CONSTRUÇÃO CIVIL - Murari, Alexandre Rodriguez; Baldan, Victor; Stamato, Guilherme Corrêa; Pablos, Javier Mazariegos; Sichieri, Eduvaldo Paulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The construction industry is the largest consumer of raw materials in the world and with the greatest environmental impact. Traditional construction systems, such as masonry, have high waste generation and low productivity. The lightweight wood frame construction system is prefabricated, with control of the production of the elements and systems, low waste generation and high execution speed. It can be a viable alternative for the reduction of the waste generated in the civil construction, mainly for the housing sector. The objective of this article is to present the characteristics of this construction system and to perform a comparative analysis of waste generation and productivity with other construction systems used in Brazil, according to NBR 15.575 (ABNT, 2013). For this, a survey of the data of the Brazilian civil construction sector and of the light frame construction system, homologated by the SINAT system was carried out.